2021
DOI: 10.4103/1995-7645.312512
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of acceptance and willingness to pay for the COVID-19 vaccine in the general public of India

Abstract: Objective: To determine the predictors of acceptance and willingness to pay (WTP) for the COVID-19 vaccine among the Indian public and to provide insights for future demand forecasts and pricing considerations. Methods: A nationwide, web-based, self-administered, cross-sectional survey was conducted from 5 to 20 October 2020. The health belief model (HBM) approach was used as a theoretical framework to assess the predictors of acceptance of and WTP for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 26 publications
7
23
0
Order By: Relevance
“…Regarding our findings with respect to the dimensions of the HBM, vaccine acceptance may be related to respondents' perceived susceptibility to COVID-19, perceived benefits of the vaccine, fewer perceived barriers of receiving the vaccine, and cues to action from doctors, family, and friends. These observations are supported by other studies' findings about influenza vaccination acceptance in Bangladesh and elsewhere [43,53,68,70]. For instance, in a study of the capital city of Bangladesh, residents were likely to vaccinate themselves and others if they were concerned about being infected by the virus [21].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Regarding our findings with respect to the dimensions of the HBM, vaccine acceptance may be related to respondents' perceived susceptibility to COVID-19, perceived benefits of the vaccine, fewer perceived barriers of receiving the vaccine, and cues to action from doctors, family, and friends. These observations are supported by other studies' findings about influenza vaccination acceptance in Bangladesh and elsewhere [43,53,68,70]. For instance, in a study of the capital city of Bangladesh, residents were likely to vaccinate themselves and others if they were concerned about being infected by the virus [21].…”
Section: Discussionsupporting
confidence: 78%
“…Regarding our study's high prevalence of COVID-19 vaccine intentions, this finding is generally consistent with other observations. Similarly, high vaccine acceptance rates have been noticed among the general population of India (89.3%), healthcare workers in Kuwait (83.3%), Australian citizens, Israeli adults, the general population of France (77.6%), pregnant women of China (77.4%), and French healthcare workers (76.9%) [9,32,[42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 93%
“…In contrast to China and Taiwan, India had a large outbreak of COVID-19 during data collection. Our study showed high vaccine acceptance, in line with other studies (e.g., ~90% vaccine acceptance according to Goruntla et al [21]). In our study, individuals from India with a personal COVID-19 diagnosis had signi cantly higher vaccination intent, and higher, though not signi cant, risk perceptions.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, individuals from India with a personal COVID-19 diagnosis had signi cantly higher vaccination intent, and higher, though not signi cant, risk perceptions. The study by Goruntla et al con rmed this nding showing that higher perceived susceptibility to infection and severity of COVID-19 infection were important factors associated with vaccine acceptance [21].…”
Section: Discussionmentioning
confidence: 85%
“…There have also been recent efforts to approve additional vaccines (such as Sputnik V and Moderna) to help meet the potential demand for vaccination in India. With the exception of Goruntla et al (2021) and Kumari et al (2021), however, there is virtually no information on attitudes, perceptions, and beliefs related to the COVID-19 vaccine in India. This is particularly pressing given the scale at which vaccination is proposed in India as well as past indications of low adult vaccination rates in India (Dash et al, 2020).…”
Section: Covid-19 Vaccination In Indiamentioning
confidence: 99%